IMPLEMENTASI MANAJEMEN STARTEGIS DI MADRASAH - Hardi, SUHARDI (Universitas Muhammadiyah Tangerang, 2024)
As part of formal educational institutions in Indonesia, madrasah are also required to realize national education goals. Therefore, madrasah must be managed with effective management in order to become superior educational institutions. Management strategy is considered as appropriate management to provide excellent educational institutions. The problem is that there are many management strategy models. It's just that not all of them are suitable for implementation in madrasah. Therefore, an in-depth analysis is needed to determine the appropriate model. The aim of this research is to analyze several management strategy models and determine the appropriate model to be implemented in madrasah. The method used is a qualitative research method in the form of a literature review. The results found that the MSBSP model is a management strategy model that is considered suitable for implementation in madrasah as Islamic educational institutions.